School principal’s training programs, challenges, and improvement opportunities: rapid review - Alladatin, Judicaël; Lionel, Roche; Insaf, Al-chikh (Universitas Majalengka, 2024)
Effective school leaders, with relevant training programs, high-quality management, and in-service pedagogical training, are recognized for their ability to positively influence student performance (Sanfo, 2020). In this study, we focus on analyzing training programs for school principals, assessing aspects such as their strengths, shortcomings, opportunities, as well as potential challenges. The aim was to identify the most effective models for training and preparing school principals in order to optimize their impact on educational success. To this end, we conducted a rapid review of 27 articles from scientific and gray literature. The results of this rapid review will be discussed with a view to an in-depth reflection on the strengths, challenges and opportunities inherent in the various training methods. The analysis shows that school principals’ training is vital in the sense that it prepares trainees for their demanding and increasingly complex future roles. However, these programs sometimes suffer from shortcomings related to the selection process, the consistency between what is taught and what is experienced in the field, and the incoherence of the content of the training curriculum. The analysis also highlighted some opportunities that could improve these programs if integrated, as well as factors that could be barriers to the correct implementation of these valuable training programs.